1991
DOI: 10.1128/mcb.11.4.2263
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous DNA replication in human cells is affected by the size and the source of the DNA.

Abstract: We previously developed short-term and long-term assays for autonomous replication of DNA in human cells. This study addresses the requirements for replication in these assays. Sixty-two random human genomic fragments ranging in size from 1 to 21 kb were cloned in a prokaryotic vector and tested for their replication ability in the short-term assay. We found a positive correlation between replication strength and fragment length, indicating that large size is favored for efficient autonomous replication in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
101
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 38 publications
8
101
0
Order By: Relevance
“…It has been reported that almost any human genomic DNA fragments longer than a certain length replicate autonomously in human cells and that the efficiency of replication varies depending on the size of the fragment (Heinzel et al, 1991). Our results also showed that not only HER segments but segments excluded during HER selection are able to replicate in human cells.…”
Section: Discussionsupporting
confidence: 76%
“…It has been reported that almost any human genomic DNA fragments longer than a certain length replicate autonomously in human cells and that the efficiency of replication varies depending on the size of the fragment (Heinzel et al, 1991). Our results also showed that not only HER segments but segments excluded during HER selection are able to replicate in human cells.…”
Section: Discussionsupporting
confidence: 76%
“…However, our findings are consistent with previous observations that found plasmid EBV-based vectors containing randomly selected large (у16 kb) human genomic DNA fragments, conferred efficient episomal replication in mammalian cells. 11,40 This may involve the presence of either additional genomic origins of replication, 11,12,40 or S/MAR elements 39 or both. While the retention of episomes within cells is clearly important, our work indicates that the maintenance of tissue-specific transgene expression from within REVs is also a crucial consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, replication efficiency varies with the size of the inserted fragment (33), suggesting either that the density of replicators in mammalian genomes is very high, or that sequence requirements for origin function in this assay are minimal, but larger fragments are more efficiently retained.…”
Section: Discussionmentioning
confidence: 99%